KEEFEKTIFAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN PENDEKATAN PROBLEM POSING PADA MATERI SEGIEMPAT KELAS VII - Muh. Khoirul Anam; Dwi Ivayana Sari; Ria Faulina (JURNAL MathEdu (Mathematic Education Journal), 2022)
The purpose of this research is generally to describe the effectiveness of the application of the discovery learning learning model by using a problem posing approach on the quadrilateral material of class VII. This research uses experimental type of quantitative research. This study took two groups, namely the first class is the control class and the second class is the experimental class with 17 students each. Data collection techniques in this study used observation and tests in the form of posttest and pretest. Based on the results of descriptive statistical analysis, it was found that the teacher's ability to manage learning using the discovery learning learning model with a problem posing approach was said to be effective, because the average aspect was in the very good category, namely 3.9. And the results of the analysis of student activity observation data are in the very good category, namely 98.81%. Based on the percentage of classical completeness of mathematics learning outcomes after the discovery learning model was applied, 100% was categorized as complete and 0% incomplete. Based on the results of the independent sample t-test, learning with discovery learning learning models with a problem posing approach is higher than students who are taught using conventional learning.